THE NEEDS OF ENGLISH FOR VOCATIONAL SCHOOLS OF AVIATION IN BANTEN PROVINCE - SELNISTIA HIDAYANI, - (2018)
Although the status of English language as the language medium for international communication and affairs influences the importance of this language to be enhanced in vocational schools, the English ability of vocational schools' graduates does not accommodate the industry's needs. Thus, this study aimed to seek the meeting point between the industry's demands and the vocational schools' curriculum. More specifically, this study examines (1) the needs for the English language at the aviation industry, (2) the curriculum demands with regard to English course at the vocational schools for aviation, (3) how the schools meet both the curriculum and industry's demands, and (4) a language program to be proposed to meet both the curriculum and industry's demands. This study is designed as a mixed-method research. This study involves one industry with 28 employees and three vocational schools of aviation with seven English teachers. The interview results are analyzed by identifying the existing codes related to their views on what needs of English language for the aviation industry must be accommodated as well as their views on the suitability of the current English language learning contents with the curriculum's and industry's demands. The questionnaire results are classified into four categories of information: personal background, language analysis, language learning process, and recruitment process. The suitability of the currently used curricula, i.e. KTSP and 2013 Curriculum and schools' syllabi is analyzed by identifying the constituting components. First, it is found that there are two types of needs: in the recruitment process and at work process. Second, it is found that the curriculum generally emphasizes the development of four English language skills, i.e. speaking, reading, listening, and writing. Third, it is found that the teachers and the industry have similar perception that the syllabus design and its implementation have not accommodated the industry's needs. Fourth, it is found that the alumni of vocational and non-vocational schools have similar opinion in the area of self-evaluation and the question of the aspects needed in the questionnaires that both need the aspects of listening, reading, knowledge or vocabulary, and writing while working. On the basis of the findings, the present study proposes a program to be considered in developing an English language program at a vocational high school for aviation. It concludes that the proposed language program for aviation schools should be based on the competence standards of the industry's needs either in the recruitment process and the work process. ;---Meskipun status bahasa Inggris sebagai bahasa pengantar di dalam komunikasi dan hubungan internasional mempengaruhi pentingnya bahasa asing ini untuk digalakkan di dalam sekolah vokasi, kemampuan berbahasa Inggris lulusan sekolah vokasi tidak mengakomodir kebutuhan industri. Oleh karena itu, studi ini bertujuan untuk mengetahui kesinambungan antara tuntutan industri dengan kurikulum bahasa Inggris di sekolah vokasi. Lebih khusus nya, studi ini mengkaji (1) kebutuhan bahasa Inggris di industri aviasi, (2) tuntutan kurikulum yang berkaitan dengan pembelajaran bahasa Inggris di sekolah vokasi bidang aviasi, (3) bagaimana sekolah tersebut memenuhi tuntutan kurikulum dan industri, dan (4) program bahasa Inggris yang diajukan untuk memenuhi tuntutan kurikulum dan industri. Studi ini di desain sebagai penelitian dengan metode campuran (mixed methods). Studi ini melibatkan satu industri aviasi yang terdiri dari 28 karyawan dan tiga sekolah vokasi aviasi yang terdiri dari tujuh guru bahasa Inggris. Hasil interviu dianalisis dengan mengidentifikasikan kode-kode yang muncul yang berkaitan dengan pandangan partisipan mengenai kebutuhan bahasa Inggris apa yang harus diakomodir untuk industri aviasi serta pandangan mereka terhadap kesesuaian antara konten pembelajaran bahasa Inggris yang ada sekarang dengan tuntutan kurikulum dan industri nya. Hasil kuesioner diklasifikasikan ke dalam empat kategori informasi: latar belakang pribadi, analisis bahasa, proses pembelajaran bahasa, dan proses rekrutmen. Kesesuaian dari kurikulum yang saat ini sedang digunakan, yaitu KTSP dan Kurikulum 2013 serta silabus dari sekolah dianalisis dengan mengidentifikasi komponen-komponen nya. Pertama, hasil analisis menunjukkan bahwa terdapat dua jenis kebutuhan berbahasa Inggris: di dalam proses rekrutmen dan di dalam proses bekerja. Kedua, kurikulum yang dipakai secara umum menekankan pada pengembangan keempat kompetensi berbahasa Inggris, yaitu berbicara, membaca, mendengarkan, dan menulis. Ketiga, para guru dan pihak industri memiliki kesamaan persepsi bahwa desain silabus dan implementasi nya belum mengakomodir kebutuhan industri. Keempat, lulusan dari sekolah vokasi dan non-vokasi juga memiliki kesamaan persepsi dalam hal evaluasi diri dan pertanyaan mengenai aspek-aspek yang dibutuhkan seperti, mendengarkan, membaca, pengetahuan kosakata, dan menulis. Berdasarkan pada temuan tersebut, studi ini mengajukan sebuah program untuk diperhatikan dalam mengembangkan sebuah pembelajaran bahasa Inggris di sekolah vokasi aviasi. Kesimpulannya yaitu program bahasa Inggris yang diajukan ini harus berdasarkan pada standar kompetensi dari kebutuhan industri baik di dalam proses rekrutmen maupun di dalam proses bekerja.